Anxiety Level and Dialysis Adequacy of Patients Chronic Kidney Diseases During Covid-19 Pandemic in Indonesia - Supriyadi; Umi Margi Rahayu; Maria Suryani (Sekolah Tinggi Ilmu Kesehatan Kendal, 2023)
There was a conflicting result of previous studies about the correlation between anxiety and dialysis adequacy. The aim of this study was to evaluate the association of anxiety level with dialysis adequacy and uncover the association of age, leucocyte, and hemoglobin with anxiety and dialysis adequacy in chronic kidney disease patients undergoing hemodialysis during the Covid-19 pandemic. A cross-sectional study was conducted on 139 patients with chronic kidney disease at a hospital in Semarang, Indonesia. The anxiety was measured by Hamilton Rating Scale for Anxiety. Urea reduction rate (URR) was calculated using a standard formula to measure dialysis adequacy. Hemoglobin and leucocyte were analyzed in the laboratory. The Pearson correlation test was used in the study. There was no significant correlation between age, hemoglobin, and leucocyte with anxiety (p>0.005) and dialysis adequacy (P>0.005). There was a significant correlation between anxiety and dialysis adequacy (r= -0.207; p=0.014).